Using shared experiences to recruit committed human intelligence sources: Exploring the shared attention mechanism and the role of social connection - Neequaye, David A. (Legal and criminological psychology, 2024)
Objectives We examined the possibility of using shared experiences to recruit human intelligence (HUMINT) sources. The research was based on two hypotheses. (a) Shared experiences amplify interpersonal affiliation, which increases the extent to which sources will commit to an intelligence arrangement. (b) The social connection opportunity shared experiences afford is what increases such commitment. Methods Participants assumed the role of a source meeting a potential handler, a police officer, to discuss an arrangement whereby they might supply intelligence. We manipulated shared experience via the meeting's setting. Half of the participants underwent a shared experience to facilitate interpersonal affiliation with the handler, and the other half did not undergo such an experience. The handler used one of two approaches to propose the arrangement. One approach afforded a social connection opportunity, and the other constrained the possibility of a social connection in the arrangement. Results The findings indicated that shared experiences can have interpersonal influence. The shared experience operationalization positively influenced felt closeness and social connection affordance. However, there was little indication that handlers could capitalize on shared experience to bolster commitment.